Biological activity of astilbin from Dimorphandra mollis against Anticarsia gemmatalis and Spodoptera frugiperda - Pereira, LGB; Petacci, F.; Fernandes, J. B.; Correa, A. G.; Vieira, P. C.; da Silva, MFGF; Malaspina, O. (Wiley-Blackwell, 2002)
Astilbin was isolated in high yield from Dimorphandra mollis, and its insecticidal and growth inhibiting activity by stomach ingestion were evaluated against Anticarsia gemmatalis and Spodoptera frugiperda. The insecticidal activity of astilbin, the weight reduction of the larval phase and the prolongation of the larval and pupal phases were verified for both species. Astilbin was identified on the base of its NMR, MS and physical data. (C) 2002 Society of Chemical Industry.
Keywords: astilbin; insecticide; Spodoptera frugiperda; Anticarsia gemmatalis; Lepidoptera; Noctuidae; Dimorphandra mollis